ChemInform Abstract: Synthesis of α, β‐Unsaturated Acylsilanes via Perrhenate‐Catalyzed Meyer—Schuster Rearrangement of 1‐Silylalkyn‐3‐ols. Issue 16 (March 2016) - Nikolaev, Andrei; Orellana, Arturo
Abstract: The title transformation of 3‐aryl, alkenyl, and alkyl substituted 1‐silylalkyn‐3‐ols as well as disubstituted derivatives thereof is investigated.